'Learn by heart': Beckett's Schoolboy Copy of Shakespeare's Macbeth. Issue 2 (September 2022) - Verhulst, Pim; Van Hulle, Dirk
Abstract : This article discusses a recently discovered copy of William Shakespeare's play Macbeth that once belonged to Samuel Beckett when he was a student at Portora Royal in 1922. Although the volume is in private hands, scans of the annotated pages are freely available in the Beckett Digital Library of the Beckett Digital Manuscript Project. Compared to other surviving works by and on Shakespeare in Beckett's possession, the Macbeth schoolboy copy shows an unusual abundance of reading traces and marginalia. However, passages that are not underlined or otherwise marked turn out to be equally important for an assessment of the play's impact on Beckett's writing, in addition to a grey zone of indeterminate or conceptual references that are harder to classify as allusions. This is especially the case when Beckett's style becomes sparser, and he explores other dramatic genres such as radio or television alongside prose and theatre. By way of introduction, the article analyses some of these instances in more detail while providing more context about the book's provenance.